Laser de baixa intensidade na modulação do processo Inflamatório na prevenção da Síndrome do insucesso da cirurgia espinhal - Holanda, Vanessa Milanesi (2013)
Every year, over one million individuals worldwide were submitted to laminectomies, with a rate failure higher than 40%. Post laminectomy epidural adhesion is implicated as a main cause of ‘‘failed back surgery syndrome’’ and associated with high risk of complications during the revision surgery. The postoperative epidural scar can cause extradural compression or dural tethering, which lead to recurrent radicular pain and physical impairment. Several studies in the literature are signalizing that Low-Level-Laser-Therapy (LLLT) is proven to be an effective tool to assist the inflammatory process and wound healing, as well to prevent infection and dehiscence. The objectives of this project are to delineate and evaluate the LLLT effects in spinal surgery. A prospective randomized, controlled trial with a total of 48 patients, who underwent to laminectomy, were divided into 2 groups, as following: in 25 randomized patients, LLLT infrared, Power = 40mW, Fluence= 7.44 J/cm2 was applied during transoperatory phase, on the laminectomy site, on the subcutaneous tissue and surrounding the wound site. In the second group, 23 patients were induced to believe that they were getting the same treatment, avoiding psychological effect, although LLLT was not operating. In those groups, C reactive protein (CRP), lactic dehydrogenase and creatine kinase (CK) were assessed in the second and fifth days after surgery, digital temperature and visual analogue scale were measured, pre and post LLLT application. The drainage output were collected in the first and second days, following surgery in both groups. Interleukins 1, 4, 6, 8 and 10 and tumor necrosis factor alpha (TNF- α) were evaluated. The results indicated temperature decrease, pain relief and accelerated wound healing in laser group. LLLT facilitates the wound cicatrization, due to a prompt resolution while acute inflammation, as suggested by the CRP chiefly drop from second to fifth postoperative day; in which the proliferation phase of healing demonstrated statistically significant values by fast fall in the laser group of CK, suggesting that these markers may guide LLLT treatment evolution. In conclusion, it was demonstrated that only three LLLT applications could assist better wound healing, reduce the lesion inflammation, decrease drainage output and promote analgesia in the PO post laminectomy with cost-effectiveness.